2023
DOI: 10.1007/s12033-023-00922-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Diagnostic Biomarkers for Compensatory Liver Cirrhosis Based on Gut Microbiota and Urine Metabolomics Analyses

Yingjun Chen,
Shaoxian Chen,
Chandi Xu
et al.

Abstract: Liver cirrhosis is one of the most prevalent chronic liver disorders with high mortality. We aimed to explore changed gut microbiome and urine metabolome in compensatory liver cirrhosis (CLC) patients, thus providing novel diagnostic biomarkers for CLC. Forty fecal samples from healthy volunteers (control: 19) and CLC patients (patient: 21) were undertaken 16S rDNA sequencing. Chromatography-mass spectrometry was performed on 40 urine samples (20 controls and 20 patients). Microbiome and metabolome data were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
1
1
0
Order By: Relevance
“…To the best of our knowledge, Agathobacter has not been reported to be associated with osteoporosis. In a study identifying diagnostic biomarkers for compensatory liver cirrhosis, Agathobacter was elevated in patients with compensatory liver cirrhosis (Chen et al, 2023). In addition, previous studies have shown that Lactobacillus was more abundant in the osteoporosis group than in the control group (He et al, 2020), which was consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…To the best of our knowledge, Agathobacter has not been reported to be associated with osteoporosis. In a study identifying diagnostic biomarkers for compensatory liver cirrhosis, Agathobacter was elevated in patients with compensatory liver cirrhosis (Chen et al, 2023). In addition, previous studies have shown that Lactobacillus was more abundant in the osteoporosis group than in the control group (He et al, 2020), which was consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…To the best of our knowledge, Agathobacter has not been reported to be associated with osteoporosis. In a study identifying diagnostic biomarkers for compensatory liver cirrhosis, Agathobacter was elevated in patients with compensatory liver cirrhosis ( Chen et al., 2023 ). In addition, previous studies have shown that Lactobacillus was more abundant in the osteoporosis group than in the control group ( He et al., 2020 ), which was consistent with our results.…”
Section: Discussionmentioning
confidence: 99%